The role of worry in exercise and physical activity behavior of people with multiple sclerosis. Issue 1 (31st December 2022) - Ware, Megan; O'Connor, Patrick; Bub, Kristen; Backus, Deborah; McCully, Kevin
ABSTRACT: Purpose: This study is a secondary analysis of data from a mixed methods exploration of fatigue in people with multiple sclerosis (MS), a chronic autoimmune disease affecting the central nervous system. During initial analysis, worry emerged during discussions of the fatigue experience. The purpose of this study is to explore worry in relationship to exercise and physical activity behavior. Methods: Mixed methods were used to address the research question. 55 people with MS provided demographic and survey data (habitual physical activity, body perception, functioning). 35 participated in semi-structured interviews on the topics of fatigue, body sensations, emotions, and their effects on physical activity. Qualitative data were analyzed utilizing constructivist grounded theory. Quantitative data were analyzed utilizing multiple regression. Results: Qualitative theory described participants' thoughts and experiences regarding the consequences of fatigue during activity, and how they appear to influence subsequent actions. Worry played a critical role in thought processes regarding physical activity. Aspects of body perception were weak quantitative predictors of physical activity behavior after control of physical functionality. Conclusions: The most significant finding of this study was the description and dialogue about worry as a factor that shapes perceptions of the benefits and value of exercise and physical activity. Physical activity practitioners could benefit from seeking to understand physical-activity-related worry when examining physical activity behavior and designing programming.